Soft set theoretic approach for discovering attributes dependency in information systems - Herawan, Tutut (2010)
This paper presents the applicability of soft set theory for discovering attribute dependency in multi-valued information systems The proposed approach is based on the notion of multi-soft sets An inclusion of value sets in soft set theory is used to discover degree of attributes dependency The results obtained are equivalent to the rough attributes dependency.